Health communication strategies to prevent pesticide exposure risks among tomato harvesters in karo regency, Indonesia: A preliminary study - Annisa, Rizka; Rochadi, Kintoko; Ashar, Taufik; Mahyuni, Eka Lestari (Medicina Historica, 2024)
In the lush fields of Karo Regency, Indonesia, tomato harvesters work tirelessly to ensure a bountiful harvest. However, with the use of pesticides to protect the crops from harmful pests, there is a looming risk of exposure to toxic chemicals. This presents a serious health concern for the farmers and their families who consume the produce. To address this issue, a comprehensive health communication strategy must be implemented to educate and empower the tomato harvesters on the risks of pesticide exposure and the preventive measures they can take to protect themselves. Community engagement is also a crucial component of a successful health communication strategy. By involving local organizations, community leaders, and government agencies, outreach programs can be organized to promote safe farming practices and raise awareness about the risks of pesticide exposure. Community members can play a key role in disseminating information and supporting the implementation of health communication activities among tomato harvesters.